2005
DOI: 10.1007/s00122-005-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of powdery mildew resistance in cucumber (Cucumis sativus L.)

Abstract: A population of F7 recombinant inbred lines (RILs) was made from a cross between susceptible ('Santou') and resistant (PI197088-1) lines of cucumber in order to study powdery mildew resistance loci. Susceptibility to powdery mildew in the F7 RIL individuals showed a continuous distribution from susceptible to resistant, suggesting that powdery mildew resistance is controlled by quantitative trait loci (QTLs). A QTL analysis identified two and three loci for powdery mildew resistance under 26 and 20 degrees C c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 36 publications
4
51
1
3
Order By: Relevance
“…This result is consistent with the results from classical genetic analysis (Table S1). The seed color trait is relatively stable and is not affected by environmental factors [49][51]. In other crops, the number of genes controlling the seed coat color trait is variable; for example, the seed color trait is regulated by a single gene in flax [52], watermelon [53], and lettuce [54], while two independent loci were found in lentil [55] and biennial white sweet clover [56], and at least three genes are involved in controlling the trait in pea [57] and capsicum [58].…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results from classical genetic analysis (Table S1). The seed color trait is relatively stable and is not affected by environmental factors [49][51]. In other crops, the number of genes controlling the seed coat color trait is variable; for example, the seed color trait is regulated by a single gene in flax [52], watermelon [53], and lettuce [54], while two independent loci were found in lentil [55] and biennial white sweet clover [56], and at least three genes are involved in controlling the trait in pea [57] and capsicum [58].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative trait loci (QTLs) associated with PM resistance have been mapped to six cucumber chromosomes [1, 2, 8, 1113]. Although these findings have provided insights into the genetic control of cucumber PM resistance, the molecular defense mechanisms of host resistance against cucumber PM remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports state that resistance is a quantitative trait controlled by multiple recessive genes (Smith, 1948;Barnes and Epps, 1956;Fugieda and Akiya, 1962;Kooistra, 1968;Kooistm, 1971;Zhang et al, 2005;Sakata et al, 2006). However, Shanmugasundarum et al (1971) differentiated between hypocotyl and leaf resistance and concluded that a recessive gene for hypocotyl resistance (pm-h) is essential for overall resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In cucumber, there are various studies about the molecular biology of PM resistance. Sakata et al (2006) detected three quantitative trait loci (QTL) for PM resistance at 20°C and two at 26°C. Of these, one major QTL was found to confer resistance at both 20° and 26°C.…”
Section: Introductionmentioning
confidence: 99%